Planning of Buildings in Tropical Environment – How Disaster changed buildings? - Erdik, Erkan (Journal of A Sustainable Global South; Vol 3 No 2 (2019): August 2019DO - 10.24843/jsgs.2019.v03.i02.p04, 2019)
As my personal heritage is from turkey and earthquakes been always something usual for me, I wanted to know how the buildings can stand such a disaster. In the following paper I would like to investigate the architecture in different parts of the world and understand how this changed the architecture by time. Also, I want to know how these influence the vernacular architecture in different countries. In the period, there has been a load of different disasters. The problem of these disasters is also mostly located in the tropics. As the climatic conditions influence the material and quality of buildings. The problems can differ in size and could occur in a big space.  To pursuit the complicate topic there will be an explanation about Earthquake, furthermore there will be several examples of such a disaster. At the end we will summarize the consequences of an earthquake with a follow up of how to design for them. Index Terms — Earthquake, EOLBREAK, Urban,  Seismic